Distance Learning: Towards a Conceptual approach Post-COVID, and a Technological Proposal for Teaching Arabic to non-native Speakers - Zighem, Yamina (LANGUAGE ART, 2024)
DistanceLearning is one of the most commonly used terms in the field of education, particularly in recent years with the emergence of the COVID-19 pandemic, which necessitated the adoption and enhancement of distance learning mechanisms. This trend is expected to continue as the demand for educational technologies, especially language learning, grows. Arabic language is not exempt from this trend, as the number of learners’ increases, presenting several challenges, particularly in terms of its computer-based processing, which has not been optimally addressed. With the expansion of distance education concepts to include modern technologies, various educational models have emerged including: Digital learning; Numbered learning; Blended learning; and Virtual learning; each with varying effectiveness in acquiring Arabic language skills based on technological choices.